2005
DOI: 10.1063/1.1884998
|View full text |Cite
|
Sign up to set email alerts
|

Site-site memory equation approach in study of density/pressure dependence of translational diffusion coefficient and rotational relaxation time of polar molecular solutions: Acetonitrile in water, methanol in water, and methanol in acetonitrile

Abstract: We present results of the theoretical study and numerical calculation of the dynamics of molecular liquids based on the combination of the memory equation formalism and the reference interaction site model (RISM). Memory equations for the site-site intermediate scattering functions are studied in the mode-coupling approximation for the first-order memory kernels, while equilibrium properties such as site-site static structure factors are deduced from RISM. The results include the temperature-density (pressure)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Further to all thermodynamic data for water in wide range of temperatures and pressures [36], molecular theory of solvation [27] equips us with the detailed knowledge about the pressure and/or temperature induced microscopic structural changes in neat water [20,21], aqueous solutions of acetonitrile and methanol [22][23][24], and tert-butyl alcohol [37]. Having that, we could not resist the temptation to check if the hydrogen bond network formation and rupture would also be responsible for such outrageous values of the slip length for water.…”
Section: Thermodynamic Dependences Of Slip Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Further to all thermodynamic data for water in wide range of temperatures and pressures [36], molecular theory of solvation [27] equips us with the detailed knowledge about the pressure and/or temperature induced microscopic structural changes in neat water [20,21], aqueous solutions of acetonitrile and methanol [22][23][24], and tert-butyl alcohol [37]. Having that, we could not resist the temptation to check if the hydrogen bond network formation and rupture would also be responsible for such outrageous values of the slip length for water.…”
Section: Thermodynamic Dependences Of Slip Lengthmentioning
confidence: 99%
“…19, the friction coefficient is inversely proportional to viscosity, so that its tremendous decrease automatically assumes an increase of friction between the solid surface and the liquid. Another and rather little contribution to ξ w,ab comes from the fact that in compression, when hydrogen bonds are ruptured, first peak of radial distribution function for oxygen sites becomes enhanced and for hydrogen sites substantially diminished [20][21][22][23][24]. We know [19] that in case of water principal contribution to the integral (3) comes from the first solvation shell of the oxygen site, while the same contribution from the hydrogen site is negligibly small.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Theoretically, Hirata and co-workers have calculated the dynamics of ions in water and other polar liquids from the molecular theory [24][25][26] based on the interaction-site model for molecular liquids and on the generalized Langevin equation combined with the mode-coupling theory. They have also provided a quantitative explanation of the pressure dependence of diffusion coefficient and orientational relaxation time of different solutes in water and some other solvents [27]. Recently, Chowdhuri and co-worker [28] have studied the importance of solvents of hydrogen bonding network on the dynamics of ions in liquid methanol and water under pressure, at 258 and 298 K. It is observed that the hydrogen-bond lifetime and structural-relaxation time of methanol are increasing monotonically with pressure and the results are more prominent at low temperatures, whereas in the case of water, an opposite trend of the hydrogen bond dynamics is observed under similar conditions.…”
Section: Introductionmentioning
confidence: 98%
“…The dielectric friction is produced by the inhomogeneity in the charge density of water, caused by the density fluctuation due to the hydrogen bond. 51 In other words, the BC becomes less slip, so the hydrodynamic radius appears larger, Figure 4.…”
mentioning
confidence: 98%